PENGENDALIAN WAKTU DAN BIAYA PEKERJAAN KONSTRUKSI SEBAGAI DAMPAK DARI PERUBAHAN DESAIN - Messah, Yunita Afliana; Lona, Lazry Hellen Paula; Sina, Dantje A. T. (Jurnal Teknik Sipil, 2013)
The purpose of this study is to describe the effect of changing control of the design that have an impact on the time and cost of construction work that affects the performance of construction work Embung Irrigation Oenaem. This study used two methods of controlling the Earned Value Analysis (EVA) and integrated method of shortening the duration of the critical path (Crashing Length) at Critical Path Method (CPM) using the application as an alternative to controlling overtime. To use of the two methods mentioned above it can be seen and obtained alternative pengedalian time and construction costs as a result of design changes that occurred in the Irrigation Development Project Embung Oenaem. Based on the analysis that had been done when a deviation occurs at 7 weeks, the total work period to 37 weeks from 30 weeks the amount of time a plan with estimated cost is Rp. 9,489,206,129.03. Then controlled using the method of shortening the duration (Crashing Length) with future application of the overtime work to 35 weeks (5 weeks delay) with the amount of the cost of Rp. 9.458.239.978,70 (excluding VAT) of the total contract value of Rp. Rp. 8.563.635.912,98 (excluding VAT 10%).